PHYSICAL PROPERTIES OF WET NOODLE BASED ON POTATO AND TAPIOCA COMPOSITE FLOUR - Zulman Efendi; Fitri Electrika D. Surawan; Yosy Sulastri (BPFP Faperta UNIB, 2016)
Wet noodle properties prepared from tapioca flour : potato flour proportion i.e. 70:30; 60:40; 50:50; 40:60; and 30:70 were studied by Complete Randomized Design. The potato flour proportion effect were significantly contributing to physical properties of strain and waterabsorption index, moisture content, and L, a, b value.The wet noodle prepared from tapioca : potato flour = 70:30; 60:40; 50:50 have no significant different on strain (?L/L) and , water absorption index, moisture content and L, a, b value.The wet noodle prepared fromtapioca :potato flour = 40:60 and 30:70 hadlower strain (?L/L) index thus giving the highest waterabsorptionand moisture content. But its noodle has lower brightness level. The result revealed the possibility of composite flour from potato and tapioca 50:50 could be produce wet noodle for functional food. Its physical properties i.e. strain and water absorption index, moisture content, and L, a, b value were 0.5, 0.37, 47.35, and 65.6, -1.0, 25.6, respectively.